The Domain of Justice and the Extension of Rights: A Reply to Macdonald on Animal Rights - Diem, William Matthew (American catholic philosophical quarterly, 2021)
Paul Macdonald recently argued that a consistent Thomist must hold, against Aquinas, that non-human animals have direct rights. I show that his arguments fail and that, on the contrary, the impossibility of brute animals having rights flows directly from the very essence of justice itself as it is understood by Aquinas.